Organizacje pozarządowe we współczesnym społeczeństwie obywatelskim - Babiak, Jerzy (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
Non-Governmental Organizations (NGOs) are one of the indicators in the assessment of whether the state operates on the principles of a civic society. NGOs are also a crucial element of public life as they cover an extensive area of activity. At the level of local communities they effectively promote their development as organizations that are close to the citizens. In the European Union they are an expression of public opinion. After WWII both the political and legal circumstances in Poland did not favor their development. An observable improvement began during the transition period at the turn of the 1980s and 1990s. The number of NGOs considerably increased at that time. Although the number of newly registered NGOs has been consistently decreasing since 2003, as has Poles’ interest in voluntary work, Polish NGOs are in quite good condition compared to their counterparts in other states of Central and Eastern Europe.
Non-Governmental Organizations in Contemporary Civil Society
Keywords: organizacje pozarządowe; społeczeństwo obywatelskie